ANALISIS LANGKAH AKTIVITAS FISIK SISWA MAN 1 KOTA TASIKMALAYA SELAMA PEMBELAJARAN PJOK - Muchammad Fathoni; Gumilar Mulya; Juhrodin (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA (UTP), 2026)
Physical activity plays an essential role in supporting adolescents’ health, and Physical Education (PE) lessons provide structured opportunities to meet daily activity recommendations. This study aims to analyze students’ step counts and physical activity levels during four PE sessions at MAN 1 Tasikmalaya using the Google Fit pedometer application. A quantitative descriptive survey with a cross-sectional approach was employed. The sample consisted of 70 tenth-grade students selected through cluster sampling. Step measurements were conducted across four sessions, each lasting 2 × 45 minutes. Data were analyzed using descriptive statistics and tertile-based categorization. The results indicated that the average student step count fell within the moderate activity category, with a relatively balanced distribution among low, moderate, and high activity groups. Male students tended to record higher step counts than female students. These findings demonstrate that PE lessons contribute meaningfully to students’ physical activity, although equal participation and intensity require improvement. The study recommends incorporating pedometer-based monitoring in schools and implementing more active, inclusive PE strategies.